Título Padrão - Lino Pauliukonis, Maria Aparecida; Assad Alvares, Claudia (Revista de Letras, 2025)
This article addresses the theme of argumentation in a broad sense and from new perspectives. It analyzes the processes of convincing and persuading the recipient, according to principles of enunciation theories. Thus, it focuses on the dynamics of the act of communication between social and discursive subjects, governed by a communication contract, developed from knowledge of knowledge and knowledge of belief, which serve as a basis for the recognition of social imaginaries. As a theoretical foundation, it starts from classical concepts of Aristotle's rhetoric, revised by the new proposals of Perelman (2000) and Amossy (2018) and adopts some assumptions of Charaudeau's Semiolinguistic theory (1992, 2008), whose focus is the projects of influence of the enunciating subject over the recipient. Thus, through a pragmatic-enunciative perspective, language is conceived as an act of staging, which aims to persuade a general and/or particular audience, by means of linguistic-discursive strategies. The functions of linguistic elements such as argumentative operators of opposition in the syntactic-semantic cohesion of statements and the role of lexical selection, capable of causing pathetic effects on the recipient, leading him to adhere to the theses presented, as well as a Graffiti, as a possibility of argumentation without words, by means of an imagetic text, are also examined.